Functionally Significant Coumarin-Related Variant Alleles and Time to Therapeutic Range in Chilean Cardiovascular Patients. (27th March 2020) - Rojo, Mario; Roco, Angela Margarita; Suarez, Marcelo; Lavanderos, Maria Alejandra; Verón, Gabriel; Bertoglia, Maria Paz; Arredondo, Annabella; Nieto, Elena; Rubilar, Juan Carlos; Tamayo, Francisca; Cruz, Daniela; Muñoz, Jessica; et al.
Despite the development of new oral agents over the last decade, vitamin K antagonists (VKAs) remain the most widely used anticoagulants for treating and preventing thromboembolism worldwide. In Chile, the Ministry of Health indicates that acenocoumarol should be used in preference to any other coumarin. Complications of inappropriate dosing are among the most frequently reported adverse events associated with this medication. It is well known that polymorphisms in pharmacokinetic and pharmacodynamic proteins related to coumarins (especially warfarin) influence response to these drugs. This work analyzed the impact of CYP2C19*2 ( rs4244285 ), CYP1A2*1F ( rs762551 ), GGCx ( rs11676382 ), CYP2C9*2 ( rs1799853 ), CYP2C9*3 ( rs1057910 ), CYP4F2 ( rs2108622 ), VKORC1 ( rs9923231 ), VKORC1 ( rs7294 ), CYP3A4*1B ( rs2740574 ), and ABCB1 ( rs1045642 ) polymorphisms on time to therapeutic range for oral anticoagulants in 304 Chilean patients. CYP2C9*3 polymorphisms were associated with time to therapeutic range for acenocoumarol in Chilean patients, and the CYP4F2 TT genotype, MDR1 A allele, CYP1A2 A allele, and CYP3A4 T allele are promising variants that merit further analysis. The presence of polymorphisms explained only 4.1% of time to therapeutic range for acenocoumarol in a multivariate linear model. These results improve our understanding of the basis of ethnic variations in drug metabolism and response to oral anticoagulant therapy. We hope that these findings will contribute to developing an algorithm for VKA dose adjustment in the Chilean population in the near future, decreasing the frequency of stroke, systemic embolism, and bleeding-related adverse events.